Cognitive enrichment for testing prosocial food-sharing in dolphin groups - Matrai, Eszter; Kwok, Shaw Ting; Tan, Ziying; Lin, Xiao; Lee, Wei-Kwan; Martelli, Paolo; Pogány, Ákos (Frontiers in Ecology and Evolution, 2024)
Cognitive enrichments have gained popularity in the past two decades in both farm animal and zoological settings. In this study, we present a cognitive enrichment device that, for the first time, allowed testing for prosocial food-sharing actions in dolphins. The device was made of a PVC tube and two caps with rope handles; one handle was fixed to the poolside whereas the other was available for the dolphins. Its internal structure kept five fish in place while maintaining a closed status. The dolphin who pulled the rope handle could not access the fish but allowed another individual to access it. Once the handle was released, however, the device closed back. The device was tested with a male and a female group, separately. The males obtained approximately a third, while the females acquired none of the fish using the device. Moreover, the males were observed to open the device more frequently and longer in the presence of their group members and with consistent roles. These results provide the first support of male dolphins’ willingness to engage in food-sharing that could be considered as an altruistic action. It also provides basis for further investigations on more detailed and long-term monitoring of the emergence and consequences of such cooperative actions.